2017
DOI: 10.22547/ber/9.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Political Institutions and the Incidence of FDI in South Asia

Abstract: This paper attempts to empirically analyse the potential effect of political institutions on the inward foreign direct investments (FDIs) in five developing nations from South Asia, namely, Pakistan, Nepal, India, Bangladesh and Sri Lanka. Making FDI implies committing resources for a long time in the host economy. Therefore, availability of stable political institutions is one of the essential foreign location requisites for the multinationals' operations. Analysing annual aggregate data for years 1970 to 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…The descriptive statistics for all the variables used in this research are given in table two. It summarises the basic information about the data, such as the mean, standard deviation, maximum, minimum and the total number of observations for each variable or their proxies (Shah, 2017b). ii.…”
Section: Descriptive Statisticsmentioning
confidence: 99%
“…The descriptive statistics for all the variables used in this research are given in table two. It summarises the basic information about the data, such as the mean, standard deviation, maximum, minimum and the total number of observations for each variable or their proxies (Shah, 2017b). ii.…”
Section: Descriptive Statisticsmentioning
confidence: 99%
“…However, it has also been observed that a not insubstantial proportion of FDI is received in areas associated with a relatively weak rule of law environment. It is suggested that locational benefits, such as large market size (e.g., China and India), as well as rich natural resources (e.g., some African states), might out-weigh the costs associated with navigating an uncertain legal environment (Li and Resnick, 2003; Perry, 2000; Shah, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The summary of all the descriptive statistics for the variables used in the analysis are given as table Hausman(1978) specification test statistic of 45.69 showed a significant difference, as pvalue was less than 1% and hence H 0 is rejected in favour of H 1, implying that only fixed effect estimator is appropriate (Shah& Khan, 2018).Breush-Pagan/Cook-Weisberg test revealed the presence of heteroscedasticity (Shah, 2017b). Thus, robust standard errors are reported in all the estimations (Shah & Afridi, 2015).Initially,Variance Inflation Factor (VIF) test revealed that multicollinearity is severe .…”
Section: Estimation Concernsmentioning
confidence: 99%